Demography and Design: Predictors of New Product Team Performance - Ancona, Deborah Gladstein; Caldwell, David F. (Organization Science, 1992)
The increasing reliance on teams in organizations raises the question of how these teams should be formed. Should they be formed completely of engineers or should they include a range of specialists? Should they be made up to people who have long tenure in the organization, or those with a wide range of experience? As teams increasingly get called upon to do more complex tasks and to cross functional boundaries within the organization, conventional wisdom has suggested that teams be composed of more diverse members. This study suggests that the answer may not be so simple. Using 409 individuals from 45 new product teams in five high-technology companies, this study investigates the impact of diversity on team performance. We found that functional and tenure diversity each has its own distinct effects. The greater the functional diversity, the more team members communicated outside the team's boundaries. This communication was with a variety of groups such as marketing, manufacturing, and top management. The more the external communication, the higher the managerial ratings of innovation. Tenure diversity had its impact on internal group dynamics rather than external communications. Tenure diversity is associated with improved task work such as clarifying group goals and setting priorities. In turn, this clarity is associated with high team ratings of overall performance. Yet diversity is not solely positive. While it does produce internal processes and external communications that facilitate performance, it also directly impedes performance. That is, overall the effect of diversity on performance is negative, even though some aspects of group work are enhanced. It may be that for these teams diversity brings more creativity to problem solving and product development, but it impedes implementation because there is less capability for teamwork than there is for homogeneous teams. These research findings suggest that simply changing the structure of teams (i.e. combining representatives of diverse function and tenure) will not improve performance. The team must find a way to garner the positive process effects of diversity and to reduce the negative direct effects. At the team level, greater negotiation and conflict resolution skills may be necessary. At the organization level, the team may need to be protected from external political pressures and rewarded for team, rather than functional, outcomes.